Comparison of Cosmetics Regulations in India and Singapore: A Regulatory Overview: Pharmaceutical Science-Pharmaceutical Analysis For Novel Drug Formulation - Kavitha N; Balamuralidhara V; Meghana M (International Journal of Life Science and Pharma Research, 2022)
Cosmetics are the fastest-growing market potential in the world and have a higher interest rate for women than men. Beauty and personal care products have often been used to enhance beauty, appearance and perfection. A blend of synthetic and herbal cosmetics thrives in India's cosmetics sector. A cosmetic product should be a complete package with all outstanding properties, such as adequate safety, efficacy, potency and marketability of the product. These characteristics are only possible with a good regulatory structure, scheme, and organisation in place. Cosmetic products are continuously revised and managed. which is the task of many regulators. The cosmetics industry has grown exponentially across the world, offering a means for a consumer to transform his or her look and make the product easily recognisable and appealing. The protection of cosmetic products is governed by various regulatory authorities around the world, each with their own set of rules and regulations that the product must follow. There are many regulatory bodies doing work efficiently. These bodies provide us with strict regulations which help us in guiding Manufacturing, Importing, Packaging, Labelling and other aspects of trade in the cosmetic industry. Cosmetic description, manufacturing specifications, licences, import regulations, labelling regulations, packaging regulations, and fee details are mentioned and also the legal authority in India (CDSCO) and Singapore (HSA) are addressed in this context and approval process of import of cosmetics has been discussed in this article. There are drugs and cosmetics legislation (D&C) in India and the Bureau of the Indian Standard (BIS), for Singapore Health products (ASEAN Cosmetic Directive) regulations 2007 under HEALTH PRODUCT ACT are discussed.